Device-associated infection rates in adult and pediatric intensive care units of hospitals in Egypt. International Nosocomial Infection Control Consortium (INICC) findings - Ossama Rasslan; Zeinab Salah Seliem; Islam Abdullorziz Ghazi; Muhamed Abd El Sabour; Amani Ali El Kholy; Fatma Mohamed Sadeq; Mahmoud Kalil; Doaa Abdel-Aziz; Hosnia Yousif Sharaf; Adel Saeed; Hala Agha; Sally Abd El-Wadood Z; et al. (Elsevier, 2012)
Summary: Purpose: To determine the rate of device-associated healthcare-associated infections (DA-HAIs) at a respiratory intensive care unit (RICU) and in the pediatric intensive care units (PICUs) of member hospitals of the International Nosocomial Infection Control Consortium (INICC) in Egypt. Materials and Methods: A prospective cohort DA-HAI surveillance study was conducted from December 2008 to July 2010 by applying the methodology of the INICC and the definitions of the NHSN-CDC. Results: In the RICU, 473 patients were hospitalized for 2930 d and acquired 155 DA-HAIs, with an overall rate of 32.8%. There were 52.9 DA-HAIs per 1000 ICU-days. In the PICUs, 143 patients were hospitalized for 1535 d and acquired 35 DA-HAIs, with an overall rate of 24.5%. There were 22.8 DA-HAIs per 1000 ICU-days. The central line-associated blood stream infection (CLABSI) rate was 22.5 per 1000 line-days in the RICU and 18.8 in the PICUs; the ventilator-associated pneumonia (VAP) rate was 73.4 per 1000 ventilator-days in the RICU and 31.8 in the PICUs; and the catheter-associated urinary tract infection (CAUTI) rate was 34.2 per 1000 catheter-days in the RICU. Conclusions: DA-HAIs in the ICUs in Egypt pose greater threats to patient safety than in industrialized countries, and infection control programs, including surveillance and guidelines, must become a priority. Keywords: Ventilator-associated pneumonia, Central line-associated bloodstream infection, Catheter-associated urinary tract infection, Developing countries, Intensive care unit, Pediatric intensive care unit